France : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This paper focuses on the corporate income tax (CIT) regime that features a high statutory rate but low revenue productivity, as well as a bias toward debt financing, ineffective size-dependent regimes, and inefficient tax incentives. Profit-insensitive taxes are comparatively high. Anti-tax-avoidance rules are strong, but risks to outbound profit shifting remain. Tax uncertainty is another concern. At the individual level, the system of taxing wealth and capital income is complex, with distortions from differential taxation across savings instruments. To address some of these issues and make the tax system more supportive of growth and job creation, the government plans to reduce the CIT rate, further cut the labor tax wedge, unify taxes on capital income, and narrow the wealth tax. Staff's analysis suggests that complementing these reforms with measures to remove inefficient tax incentives, further reduce the debt bias, address disincentives to company growth, and streamline the taxation of long-term savings could enhance their impact on competitiveness, revenues, and growth.